TEST STUDY ON CAVITATION RESISTANCE PERFORMANCE OF 17-4PH BLADE STEEL MATERIAL UNDER HUNDERD-MICRON ARRAY GROOVES STRUCTURE - DI Juan; HE Lei; WANG Chengbo; FAN Zhihang; PENG Chaoyi (Jixie qiangdu)
As a common material for flow components, 17-4PH(0Cr17Ni4Cu4Nb) martensitic stainless steel is vulnerable to serious cavitation damage. Based on the corrosion inhibition effect of array texture structure， this study focused on the cavitation characteristics and inhibition mechanism of 17-4PH material under the surface structure of hundred-micron groove array. Based on the ultrasonic cavitation test platform, the experimental data were obtained by the weight loss method, and the data points were fitted by Logistic equation to obtain the nominal incubation period and other parameters. The results show that the surface groove target with groove spacing W and groove width L in the range of hundred-micron has a good inhibitory effect on cavitation damage. The geometric parameters of the groove array structure with the appropriate ratio can further reduce the cavitation damage of the material. The groove array target with groove width L=700 μm and groove spacing W=400 μm has the longest incubation period (22.79 h) and the smallest cumulative mass loss (10.92 mg) after continuous cavitation for 50 h, thereby exhibiting the best cavitation resistance. This study can provide reference for practical engineering applications in preventing cavitation erosion.